PENGEMBANGAN STRATEGI PEMASARAN BISNIS MODEL KANVAS PADA PT PENTARIO LIBERIA PERSADA (KebunSayur Surabaya) - Irra Chrisyanti Dewi; Mega Intan Permatasari (Jurnal MEBIS (Manajemen dan Bisnis), 2018)
The purpose of this research is to describe and design marketing strategy of business canvas model. The results show that business canvas and SWOT analysis are very helpful in developing marketing strategy. The customer segment element develops into B2R; element value propositions give customers easy access to information and get KSS products; channel elements focus on the liveliness of the admin in choosing the right social media; the customer relationships element develops a strategy for customers to purchase more KSS products and be loyal to KSS products; revenue streams elements are increased through visits and workshops; elements of key resources are land in the city and hydroponic facilities; key activities elements lie in the process of growing vegetables and taking care of hydroponics equipment; key key partnerships come from raw material suppliers, farmers' partners, and processed products partners; last element cost structure over fixed costs and variable costs. The SWOT analysis assists in facing threats and taking on existing opportunities, as well as minimizing existing weaknesses.